Smart parenting program on parenting behavior and the risk of behavioral problems among a dyad of school children and their parents - Sam, Beryl Juliet; Devadason, Jeyaseelan Manickam (Journal of Asian Scientific Research, 2024)
The study examines the impact of smart parenting program on parenting behavior and the risk of behavioral problems among schoolchildren. Behavioral problems are certain disruptive actions that may be seen in various patterns in all age groups of children. This study sought to evaluate the effect of a researcher-designed SMART parenting program on parenting behavior and the risk of behavioral problems among schoolchildren and their parents in selected corporation schools in Coimbatore City, Tamil Nadu. A quantitative research approach with a pre- and post-test with a Control Group Design was adopted. Totally, 1202 schoolchildren between 8-13 years old were screened, and 129 children were identified as being at risk. The SMART Parenting program was administered to the parents in experimental group. The results of the study revealed a significant increase in parenting behavior and a decrease in the risk of behavioral problems after intervention among the children in the experimental group. An analysis of the impact of the SMART parenting programme on both groups revealed a noteworthy enhancement in parenting behaviour and a decrease in the risk of behavioural problems among parents and children in the experimental group. The SMART parenting program was highly effective in promoting parenting behavior and reducing the risk of behavioral problems among school children. Therefore, it can be widely used by school authorities, by community health nurses, and also by pediatric nurses in hospital settings.